The volatility of volatility: measuring change in party vote shares - Casal Bertoa, Fernando; Deegan-Krause, Kevin; Haughton, Tim (Elsevier, 2017)
Volatility is a widely used term in political science, but even the most widely used measure of volatility, Pedersen's index, can mask as much as it reveals. His simple and elegant calculation has become part of the political science toolbox, but scholars employing this tool have tended to produce distinctly different results thanks to a series of decisions about measurement and classification. Using examples from Central Europe the critical role of decisions related to party continuity and threshold of inclusion are identified. The article not only unpacks the underlying questions addressed by different uses of Peder- sen's index, but offers standards for choosing particular methods over others and outlines steps that should be followed in creating a more accurate measure of volatility.